2014
DOI: 10.4103/2230-8210.145043
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in adolescents

Abstract: The prevalence of severe vitamin D deficiency (VDD) in adolescents is variable but considerably high in many countries, especially in Middle-east and Southeast Asia. Different factors attribute to this deficiency including lack of sunlight exposure due to cultural dress codes and veiling or due to pigmented skin, and less time spent outdoors, because of hot weather, and lower vitamin D intake. A potent adaptation process significantly modifies the clinical presentation and therefore clinical presentations may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
1
14
0
1
Order By: Relevance
“…The prevalence of 25 (OH) vitamin D deficiency in adolescents is different, but considerably high in many regions, like Middle-east and South-East Asia. High prevalence of 25 (OH) vitamin D deficiency in Iran is similar to the results of other studies in Middle East areas, 75.1 % of women and 72.1 % of men in Iran have different level of 25 (OH) vitamin D deficiency [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 86%
“…The prevalence of 25 (OH) vitamin D deficiency in adolescents is different, but considerably high in many regions, like Middle-east and South-East Asia. High prevalence of 25 (OH) vitamin D deficiency in Iran is similar to the results of other studies in Middle East areas, 75.1 % of women and 72.1 % of men in Iran have different level of 25 (OH) vitamin D deficiency [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 86%
“…8,9 Studies conducted in different parts of Pakistan have also shown a high occurrence of hypovitaminosis D. [10][11][12] In India, studies from many parts of the country have also reported a high prevalence of hypovitaminosis D in their youths. 13,14 Vitamin D deficiency is fairly prevalent all over the globe. However, data about vitamin D status among Afghan adolescents is lacking due to scarcity of research on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…In severe and prolonged deficiency, vertebral compression fractures and fractures of the long bones may occur. Moreover, VDD can be misdiagnosed as fibromyalgia, chronic fatigue syndrome, or simply depression in adolescents (13,36,37). …”
Section: Discussionmentioning
confidence: 99%